Effect of Oregano (Origanum vulgare) Extract on Kidney Histomorphometry and Histopathology in Mice (Mus musculus) Colibacillosis Model: Pengaruh Pemberian Ekstrak Oregano (Origanum vulgare) terhadap Histomorfometri dan Histopatologi Ginjal pada Mencit (Mus musculus) Model Kolibasilosis - Alviano, Bian Febry Rohmana; Amri, Indah Amalia (Faculty of Veterinary Medicine Universitas Brawijaya, 2023)
Colibacillosis is a disease that infects the digestive tract due to infection with the pathogen Escherichia coli. E. coli is able to cause bacteremia so that E. coli can reach the kidney through blood flowing to the kidney. To reduce the side effects of treatment using antibiotics, the herbal medicine oregano (Origanum vulgare) which contains phenols (carvacrol and thymol) works as an antibacterial. The benefits of this research are as a source of information and the basis for further research related to the use of oregano extract in the treatment of colibacillosis due to E. coli infection. The study used 20 male mice, divided into 5 applicable groups, namely K-, healthy mice were not given any treatment; K+ was induced by Streptomycin 20 mg and infected with E.coli 3 x 109 CFU/ml, 0.5 ml; P1 was induced by Streptomycin 20 mg and infected with E.coli 3 x 109 CFU/ml, 0.5 ml + Origanum vulgare extract 25 mg/kg; P2 was induced by Streptomycin 20 mg and infected with Escherichia coli 3 x 109 CFU/ml, 0.5ml + Origanum vulgare extract 50mg/kg; P3 was induced by Streptomycin 20 mg and infected with E.coli 3 x 109 CFU/ml, 0.5 ml + Origanum vulgare extract 100 mg/kg. Kidney was taken for histopathological preparations with hematoxylin eosin (HE) staining. After that, it was analyzed using Kruskal Wallis and continued with Mann Whitney. Histomorphometry semiquantitative measures the width of the Bowman's glomerular capsule and the length of the tubular lumen and then analyzed using One Way Analysis of Variance (ANOVA). The results of this study showed that oregano extract had an effect on histomorphometry and histopathology of renal, with an optimal dose is 5 mg/mice.